2010
DOI: 10.1159/000315924
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Activity Level and Septic Shock: A Possible Role for Specific Anti-Endotoxin Therapy?

Abstract: Endotoxin activity (EA) plays an essential role in sepsis syndrome pathogenesis. There has been considerable interest in measuring and removing EA to predict and improve the morbidity and mortality of patients with sepsis. We performed a prospective study to assess the prevalence of EA in critically ill patients and its association with organ dysfunction and outcome, as well as in septic shock. EA (EAA(TM)) was measured within 24 h from onset of refractory septic shock in an intensive care unit. Our study demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…The usefulness of the EAA has been reported mainly in other clinical trials. 13,14 On the whole, our results suggested that the EAA values, which was correlated the most with lung injury according to the PiCCO monitoring, reflect inflammatory reactions in the lungs.…”
Section: Discussionmentioning
confidence: 63%
“…The usefulness of the EAA has been reported mainly in other clinical trials. 13,14 On the whole, our results suggested that the EAA values, which was correlated the most with lung injury according to the PiCCO monitoring, reflect inflammatory reactions in the lungs.…”
Section: Discussionmentioning
confidence: 63%
“…With increasing EA levels clot formation becomes faster and firmer in patients with early systemic inflammation, independent of cause (non-infectious or infectious) or severity. With the development of endotoxin neutralizing therapeutic options, the further understanding of the link between systemic inflammation and coagulation might be of relevance [25]. …”
Section: Resultsmentioning
confidence: 99%
“…It is thought that endotoxin translocates in the context of gastrointestinal hypoperfusion and gut failure. Thereby, EA in the blood seems to mainly reflect organ dysfunction with regard to the integrity of the gut, which can be observed in patients with SIRS, Gram positive or Gram negative sepsis [25,26]. In patients with systemic inflammation caused by infection, that is, sepsis, EA levels tend to be higher.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, EA level has been found to correlate with severity of illness indices such as the APACHE II and SOFA scores (11). Monti et al showed that patients with high EA level who met criteria for septic patients were in need of a significantly higher dose of norepinephrine and epinephrine than were patients with intermediate and low EA levels (31 ). In both studies, however, increasing EA level did not predict an increased risk of mortality.…”
Section: Table 3 Areas Under the Receiver Operating Characteristic Cmentioning
confidence: 99%